PERTUMBUHAN IKAN NILA YANG DIBUDIDAYAKAN PADA SISTEM AKUAPONIK DENGAN PADAT TEBAR YANG BERBEDA - Khadijah Irania; I Wayan Arthana; Gde Raka Angga Kartika (Program Studi Budidaya Perairan Universitas Mataram, 2022)
Aquaponics is a combination of aquaculture technology with hydroponic technology in one system to create a symbiotic relationship between the two. The main component in the aquaponics system is fish, where fish waste and feed residues as a nutrient supply are very dependent on aquatic plants. Stocking density is one of the things that needs to be considered in aquaponic fish farming systems. Inappropriate increase in stocking density can cause adverse effects that are detrimental to farmers. This study aims to determine the best growth and density level of tilapia reared in aquaponics system. The research was carried out for 40 days in April-June 2022 at the Fisheries Laboratory, Faculty of Marine Affairs and Fisheries, Udayana University, Bali. The research design used was a completely randomized design (CRD) with 3 (three) treatments and each treatment consisted of 3 replications. The stocking density used was treatment I with a stocking density of 100 fish, treatment II 150 fish, treatment III 200 fish. The results of the study concluded that different fish stocking densities had an effect on survival, weight growth and specific growth rates. The highest survival rate was found in treatment III with an average of 87.3%, the highest weight growth was found in treatment I with an average of 3.29 grams, and the highest specific growth rate was found in treatment I of 4.67%.